Dove arising - Bao, Karen (New York : Viking, 2015)
On a lunar colony, fifteen-year-old Phaet Theta does the unthinkable and joins the Militia when her mother is imprisoned by the Moon's oppressive government.
Keywords: Space colonies -- Fiction; Science fiction